Mental causation: an evolutionary perspective - Lacalli, Thurston (Frontiers in Psychology, 2024)
The relationship between consciousness and individual agency is examined from a bottom-up evolutionary perspective, an approach somewhat different from other ways of dealing with the issue, but one relevant to the question of animal consciousness. Two ways are identified that would decouple the two, allowing consciousness of a limited kind to exist without agency: (1) reflex pathways that incorporate conscious sensations as an intrinsic component (InCs), and (2) reflexes that are consciously conditioned and dependent on synaptic plasticity but not memory (CCRs). Whether InCs and CCRs exist as more than hypothetical constructs is not clear, and InCs are in any case limited to theories where consciousness depends directly on EM field-based effects. Consciousness with agency, as we experience it, then belongs in a third category that allows for deliberate choice of alternative actions (DCs), where the key difference between this and CCR-level pathways is that DCs require access to explicit memory systems whereas CCRs do not. CCRs are nevertheless useful from a heuristic standpoint as a conceptual model for how conscious inputs could act to refine routine behaviors while allowing evolution to optimize phenomenal experience (i.e., qualia) in the absence of individual agency, a somewhat counterintuitive result. However, so long as CCRs are not a required precondition for the evolution of memory-dependent DC-level processes, the later could have evolved first. If so, the adaptive benefit of consciousness when it first evolved may be linked as much to the role it plays in encoding memories as to any other function. The possibility that CCRs are more than a theoretical construct, and have played a role in the evolution of consciousness, argues against theories of consciousness focussed exclusively on higher-order functions as the appropriate way to deal with consciousness as it first evolved, as it develops in the early postnatal period of life, or with the conscious experiences of animals other than ourselves. An evolutionary perspective also resolves the problem of free will, that it is best treated as a property of a species rather than the individuals belonging to that species whereas, in contrast, agency is an attribute of individuals.